Impact of microfinance scheme towards quality of life amongst the rural dweller's in Abia state of Nigeria - Onyebuchi, Umeh Valentine; Abu Samah, Asnarulkhadi; Zawawi, Dahlia (Human Resource Management Academic Research Society, 2020)
Poverty is a global and multi-dimensional issue that affect community’s life. Poverty in its most general sense is the lack of necessities, basic food, shelter, medical care, and safety which influence the quality of life. Quality of life is a complex concept that incorporates many aspects of life, both material and non-material. Like many developing countries, in Nigeria, microfinance scheme plays a great role in improving the quality of life of its beneficiaries. This study is to examine the impact of microfinance scheme towards quality of life amongst the rural dwellers in Abia State of Nigeria. Specifically, this study examined the level of attitude, subjective norms, participation and quality of life among microfinance beneficiaries. This study also measured the mediating effect of participation on the relationship between attitude and subjective norm and quality of life. Simple stratified random sampling was used to select 391 respondents. The study covers all the 17 local government area of Abia State residents. Data was collected using developed questionnaires based on literature, concepts and related theory. The instruments were designed with 5 Likert scale and consists of five sections namely: the respondent’s profile, attitude, subjective norm, participation and quality of life. Descriptive and inferential statistic such as Pearson correlation, and multiple regression was utilized to measure the relationship between the variables studied. The findings showed that there is a significant relationship between attitude, subjective norms, participation and quality of life. Findings also revealed that there is a mediating effect of participation between attitude and quality of life. Similarly, analysis also revealed that there is a mediating effect of participation between subjective norms and quality of life. This means that participation in microfinance scheme has strong impact towards improving the quality of life for the rural dwellers in Abia State of Nigeria. This study also indicates that microfinance scheme initiated by the government is a tool for rural community development. As such, this initiative, as a form of economic community development, has the potential to be implemented on a wider scale to improve the life of the rural community in Nigeria.